Total Flavone of Abelmoschus manihot Ameliorates TNBS-Induced Colonic Fibrosis by Regulating Th17/Treg Balance and Reducing Extracellular Matrix - Qiao, Lichao; Fang, Lei; Zhu, Junyi; Xiang, Yu; Xu, Haixia; Sun, Xueliang; Chen, Hongjin; Yang, Bolin (Frontiers in Pharmacology, 2021)
Background and Aims Surgery remains the major available strategy in inflammatory bowel disease (IBD) fibrotic strictures because no available drugs have sufficient prevention and treatment in this complication. This study aimed to evaluate the efficacy of the total flavone of Abelmoschus manihot L. Medic (TFA) on the development of colonic fibrosis in mice and its possible mechanism. Methods The 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced chronic colonic inflammation-associated fibrosis mice were used to evaluate anti-fibrosis of TFA using macroscopic, histological, immunohistochemical analyses, ELISA, Masson staining, Verhoeff’s Van Gieson Staining, transcription-quantitative polymerase chain reaction, and immunoblot analysis. Results Oral administration of TFA attenuated body weight loss, reduced colon length shortening, lowered the morphological damage index score, and notably ameliorated the inflammatory response. TFA downregulated pro-inflammatory cytokines IL-6, IL-17, TNF-α, IFN-γ productions and increased the levels of anti-inflammatory cytokine IL-10 and TGF-β. The histological severity of the colonic fibrosis was also notably improved by the TFA treatment and associated with a significant reduction in the colonic expression of col1a2, col3a2, Hydroxyproline. TFA inhibits α-SMA, TGF-β, vimentin, TIMP-1 expression, increase MMPs, thereby inhibiting activated intestinal mesenchymal cells and extracellular matrix (ECM) deposition. Conclusion Together, we herein provide the evidence to support that TFA restoring the imbalance of Th17/Treg and decrease generation of ECM. This may be a potential mechanism by which TFA protects the intestine under inflammatory conditions and act as a therapeutic agent for the treatment of intestinal fibrosis in Crohn’s disease.